2010
DOI: 10.1152/jn.00190.2010
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Anisotropies in Human Visual Cortex

Abstract: senting the orientation of features in the visual image is a fundamental operation of the early cortical visual system. The nature of such representations can be informed by considering anisotropic distributions of response across the range of orientations. Here we used functional MRI to study modulations in the cortical activity elicited by observation of a sinusoidal grating that varied in orientation. We report a significant anisotropy in the measured blood-oxygen leveldependent activity within visual areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
98
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 55 publications
(66 reference statements)
22
98
1
Order By: Relevance
“…The orientation of the plaid is defined as that midway between the two grating components. The cortical responses to gratings resemble the results of Mannion et al (2010); in V1, the response to the gratings is greatest at obliques, weakest at horizontal, and intermediate for vertical orientations. Furthermore, in agreement with experiment 1, the plaid stimuli evoke a greater BOLD response than the gratings from all cortical areas.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…The orientation of the plaid is defined as that midway between the two grating components. The cortical responses to gratings resemble the results of Mannion et al (2010); in V1, the response to the gratings is greatest at obliques, weakest at horizontal, and intermediate for vertical orientations. Furthermore, in agreement with experiment 1, the plaid stimuli evoke a greater BOLD response than the gratings from all cortical areas.…”
supporting
confidence: 63%
“…However, there are a number of plausible models described below that cannot be distinguished by these data. To address this issue, we conducted a second experiment comparing orientation response profiles for plaids with those for their component gratings.We have recently demonstrated that several of the areas of human early visual cortex have anisotropic orientation tuning (Mannion et al 2010; see also Saproo and Serences 2010;Swisher et al 2010). The BOLD response in V1 is typically greatest at the obliques, weaker at vertical orientations, and weakest at horizontal orientations.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This would be analogous to the anisotropies found in orientation-tuned channels, that are thought to underlie our superior discrimination ability about vertical and horizontal relative to oblique orientations (Girshick et al, 2011;Li et al, 2003;Mannion, McDonald, & Clifford, 2010;Storrs & Arnold, 2015a). Badcock et al (2014) recently communicated via a conference abstract that they had measured spatially-contingent aspect ratio aftereffects, and also concluded that aspect ratio adaptation involves a local repulsion.…”
Section: Discussionmentioning
confidence: 63%
“…M. used functional near-infrared spectroscopy to measure the oxygenated hemoglobin response and also found the magnitude of response to be greatest in response to obliquely oriented gratings, though the differences were only significant in the left occipital lobe. This anisotropic response was also found in a greater blood-oxygen-level-dependent (BOLD) signal for obliques by Mannion, McDonald and Clifford (2010) in V1, V2, V3 and V3A/B using oriented sinusoidal gratings as stimuli. Nasr and Tootell (2012) tested the idea that the orientation bias arises at a higher visual area than V1/V2.…”
Section: Class 1 Oblique Effectsmentioning
confidence: 56%